KEMAMPUAN PREDIKSI LABA DAN ARUS KAS DALAM MEMPREDIKSI LABA DAN ARUS KAS PADA MASA MENDATANG - YANIARTHA S, P. D’YAN (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 6 No 2 (2011), 2011)
Capital market is a long-term source of fund. The exsistence of this institution is not only as a financial source, but also as an investment opportunity that involves the entire potential domestic as well as foreign public funds. In investment decision, investors need predictions to minimize risk. In this case, profit and cash flows are considered as sufficient sources of information. This research aims to examine profit and cash flows predictability.
Keywords: capital market, investment, risk, profit, cash flow